ANALISIS KANDUNGAN UNSUR HARA N, P dan K PADA HASIL PENGOMPOSAN LIMBAH PADAT KAMPUS DENGAN PENAMBAHAN EM-4 SEBAGAI RANCANGAN BOOKLET MATAPELAJARAN BIOLOGI SMA - Gunawan, Fachrul; Suwondo, Suwondo; Wulandari, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the nutrient content of composting campus solid waste with the addition of EM-4 with 4 different composting techniques and to see better and more efficient composting techniques, as well as to produce a booklet design as teaching material in biology class XII semester SMA semester. II. This research was conducted at the Compost Shop of the Natural Science Laboratory for Biology Education FKIP, Riau University, consisting of two stages, namely experimentation and booklet design which were carried out in October-December 2020. Experiments using 4 different composting techniques. The treatment given was in the form of giving EM-4 solution. The composting techniques used include: drum technique, takakura technique, bokhasi technique and hollow brick technique. The parameters measured included the nutrient content of C / N, N, P and K ratios. The results showed that differences in composting techniques for campus solid waste also had an effect on the resulting nutrient content, the C / N ratio in composting results had reached the SNI value for the C / ratio. Those who reached SNI were drum technique 15.58, takakura technique 18.71, bokhasi technique 13.02 and hollow brick technique 17.73. The N nutrient content in the composting results, the bokhasi composting technique was higher than the other techniques, namely 1.40%, the P nutrient content of the drum composting technique was higher than the other techniques, namely 0.23%, while the highest K nutrient content was the bokhasi composting technique. that is 0.24%. The experimental results are used for the design of the booklet as teaching material on waste treatment materials for Biology subjects in class XII SMA.Key Words: Booklet, composting, waste, EM-4